The impact of products exchange in multi-levels multi-products distribution network - Benfriha, Abdennour -Ilyas; Triqui-Sari, Lamia; Bougloula, Aimade-Eddine; BENNEKROUF, Mohammed (Second International Conference on Embedded & Distributed Systems (EDiS), 2020)
In this paper we analyze a problem of inventory management in a multi-levels multi-products distribution network with three echelon, the studied system consists of a central warehouse and three distribution centers identified by their location zones where each center is connected to a wholesaler group that serve the retailers of his region, which in turn feeds the customers of the regions located in the Algerian territory. The aim of this study is to apply a collaboration between the different actors of the same level in a form of an exchange of products, the exchange can occurs only when the actual demand is being received, in order to study the impact of product exchanges in the distribution networks and its influence on the total costs of the logistics chain from the central warehouse to the delivery to the final customer.